Hubungan Antara Penerimaan Diri dengan Kebermaknaan Hidup pada Narapidana di Lembaga Pemasyarakatan Kelas II A Tanjung Raja - Mella Libranti; Sawi Sujarwo (Lembaga Teewan Journal Solutions, 2026)
This study aimed to examine the relationship between self-acceptance and meaning in life among inmates aged 35–55 years at Class II A Tanjung Raja Correctional Institution. A quantitative approach was employed using simple linear regression analysis on 100 respondents. Data were collected using the Self-Acceptance Scale and the Meaning in Life Scale, both of which had undergone validity and reliability testing. The results indicated that the Self-Acceptance Scale consisted of 17 valid items with good reliability (α = 0.835), while the Meaning in Life Scale consisted of 11 valid items with very high reliability (α = 0.971). Regression analysis revealed a positive and significant relationship between self-acceptance and meaning in life (β = 0.206; p = 0.040). Self-acceptance accounted for approximately 4.2% of the variance in meaning in life. These findings suggest that self-acceptance serves as a psychological factor contributing to inmates’ sense of meaning in life, although its effect is relatively modest. The study highlights the importance of fostering self-acceptance to support psychological well-being and personal growth among incarcerated individuals.